Prevalence of blaCTX-M, blaTEM, and blaSHV Genes of Extended-Spectrum Beta Lactamase-Producing Escherichia coli in Aquaculture in Asia: A Systematic Review - Tolentino, Allysah Rhein C.; Opeda, Alyanna Renae P.; Naniong, Lorraine L.; Paralejas, Lea Janine I.; Porciuncula, Faith Marie M.; Getuiza, Irah Mae A.; Evangelista, Czarene Bon Harvey G.; Tolenada, Charlene Princess S. (Asian Journal of Biological and Life Sciences)
Extended-spectrum β-lactamase (ESBL)-producing Escherichia coli (ESBL-EC) isolates identified by their virulence factors and pathogenicity constituted a significant threat to public health in aquaculture and other water sources not only in developing countries but in Asian countries. Asia dominates aquaculture globally. Aquaculture products are internationally traded commodities that could be a significant contributor to the emergence of antibiotic-resistant bacteria in the aquatic environment when found to be contaminated. Therefore, the researchers aim to determine the presence of ESBL-EC genes in aquaculture and its potential health risks in human transmissions. Experimental and scientific studies that reported the presence of blaCTX-M, blaSHV and blaTEM genes of ESBL-EC in Asia aquaculture were reviewed from 2016 to 2022. A total of eight (8) studies were included in this review which revealed the presence of ESBL-EC genes in the South (68.0%), West (18.9%), Southeast (12.5%), and East (0.6%) Region of Asia, with the former having the highest proportion. Among the genes detected, blaCTX-M is the most isolated followed by blaSHV and blaTEM genes. The domination of Asia in aquaculture production globally has shown increased importance in effectively dealing with environmental and anthropogenic issues that allow the interactions among diverse bacteria in the aquatic environment leading to the transmission, acquisition, and rapid spread of ESBL-EC resistance genotypes in the aquaculture.
Keywords: Aquaculture; Asia; blaCTX-M; Contamination; ESBL-producing E. coli